Effects of organic fertilizer replacing chemical fertilizer on organic carbon mineralization and active carbon fractions in yellow paddy soil of Guizhou Province - Jie Wei; Sanwei Yang; Xiaoli Wang; Jianjun Duan; Ting ting Mei; Mingrui Li; Shengmei Yang; Fangchi Wang (PLoS ONE, 2025)
The aim was to decrease chemical fertilizer use and improve soil carbon sequestration. Replacing 50% chemical nitrogen fertilizer with organic fertilizer can inhibit the mineralization of organic carbon in yellow paddy soil by increasing the active organic carbon components. Four fertilization treatments (no fertilization, conventional fertilization, 50% organic fertilization and 50% chemical nitrogen fertilization, and organic fertilization instead of chemical nitrogen addition) were used to investigate the effects of using organic fertilizer instead of chemical fertilizer on soil organic carbon mineralization and active organic carbon components in paddy fields. The soil organic carbon, total nitrogen, available phosphorus, and available potassium contents were markedly higher for the organic fertilizer treatment than the no fertilization treatment. Compared with the application of chemical fertilizer alone, the substitution of chemical fertilizer with organic fertilizer significantly increased soil pH and significantly decreased the content of available potassium. The cumulative soil organic carbon mineralization rates for all treatments decreased during the incubation period. The ROC, dissolved organic carbon, and MBC contents were in 24.46%, 55.45%, and 17.60% higher, respectively, before and 19.34%, 74.98%, and 66.83%, respectively, after mineralization for 50% organic fertilization than no fertilization. Compared with the single application of chemical fertilizer, the ROC and DOC in the 1/2NPKM treatment increased significantly by 10.32% and 56.03% respectively after mineralization (p < 0.05), while the MBC in the M treatment decreased significantly by 12.05% before and 27.05% after mineralization (p < 0.05). The decrease in ROC was the most significant. Soil organic carbon mineralization was negatively correlated with SOC and active carbon fractions, and SOC was positively correlated with active carbon fractions. In summary, replacing 50% of chemical fertilizer with organic fertilizer inhibited soil organic carbon mineralization, which would improve carbon sequestration and fertilization. ROC and MBC were the main organic carbon sources mineralized.